2022
DOI: 10.1097/j.pain.0000000000002821
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for fentanyl dose requirement and postoperative pain using clinical and genetic factors in patients undergoing major breast surgery

Abstract: Fentanyl exhibits interindividual variability in its dose requirement due to various nongenetic and genetic factors such as single nucleotide polymorphisms (SNPs). This study aims to develop and cross-validate robust predictive models for postoperative fentanyl analgesic requirement and other related outcomes in patients undergoing major breast surgery. Data regarding genotypes of 10 candidate SNPs, cold pain test (CPT) scores, pupillary response to fentanyl (PRF), and other common clinical characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…These models accurately predicted odynophagia during lung cancer RT, revealing their effectiveness in pain prediction during the course of treatment for lung cancers. Studies conducted by Sun et al (2023) [32], Juwara et al (2020) [33], Lotsch et al (2017) [23], Lotsch et al (2018) [36], Sipila et al (2012) [44], Lotsch et al (2018) [34] and Wang et al (2021) [27], investigated various ML models for persistent/chronic pain prediction and features identification in post-surgery in breast cancer patients. Studies by Sun et al (2023) [32] and Juwara et al (2020) [33] revealed that the novel ML approaches, including RF, GBM, and XGBoost, exhibited higher performance in predicting Chronic Postsurgical Pain (CPSP) over the traditional regression models.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These models accurately predicted odynophagia during lung cancer RT, revealing their effectiveness in pain prediction during the course of treatment for lung cancers. Studies conducted by Sun et al (2023) [32], Juwara et al (2020) [33], Lotsch et al (2017) [23], Lotsch et al (2018) [36], Sipila et al (2012) [44], Lotsch et al (2018) [34] and Wang et al (2021) [27], investigated various ML models for persistent/chronic pain prediction and features identification in post-surgery in breast cancer patients. Studies by Sun et al (2023) [32] and Juwara et al (2020) [33] revealed that the novel ML approaches, including RF, GBM, and XGBoost, exhibited higher performance in predicting Chronic Postsurgical Pain (CPSP) over the traditional regression models.…”
Section: Resultsmentioning
confidence: 99%
“…• Cancer pain prediction • Post cancer treatment pain prediction • Cancer pain analgesics requirement Random Forest (RF) [24], [32], [33], [34], [26], [35], [27], [36], [37], [16], [10], [38], [39], [40], [41] An ensemble approach that combines the output of multiple decision trees to reach a single high accurate result. It provides a good predictive performance, low overfitting, and easy interpretability.…”
Section: Classificationmentioning
confidence: 99%
See 3 more Smart Citations